4‐Aminophthalimide Amino Acids as Small and Environment‐Sensitive Fluorescent Probes for Transmembrane Peptides. (12th November 2019) - Wörner, Samantha; Rönicke, Franziska; Ulrich, Anne S.; Wagenknecht, Hans‐Achim
Abstract: Fluorescence probing of transmembrane (TM) peptides is needed to complement state‐of‐the art methods—mainly oriented circular dichroism and solid‐state NMR spectroscopy—and to allow imaging in living cells. Three new amino acids incorporating the solvatofluorescent 4‐aminophthalimide in their side chains were synthesized in order to examine the local polarity in the α‐helical TM fragment of the human epidermal growth factor receptor. It was possible to distinguish their locations, either in the hydrophobic core of the lipid bilayer or at the membrane surface, by fluorescence readout, including blue shift and increased quantum yield. An important feature is the small size of the 4‐aminophthalimide chromophore. It makes one of the new amino acids approximately isosteric to tryptophan, typically used as a very small fluorescent amino acid in peptides and proteins. In contrast to the only weakly fluorescent indole system in tryptophan, the 4‐aminophthalimide moiety produces a significantly more informative fluorescence readout and is selectively excited outside the biopolymer absorption range. Abstract : Beat tryptophan ! The 4‐aminophthalimido system as an amino acid side chain component is isosteric with the tryptophan indole moiety but shows much more powerful and polarity‐sensitive fluorescence. With the aid of amino acids incorporating this moiety it was possible to use fluorescence readout to examine the local polarity in the α‐helical transmembrane fragment of the human epidermal growth factor receptor.